2018
DOI: 10.1364/ol.43.002611
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence correction with artificial neural networks

Abstract: We design an optical feedback network making use of machine learning (ML) techniques and demonstrate via simulations its ability to correct for the effects of turbulent propagation on optical modes. This artificial neural network scheme relies only on measuring the intensity profile of the distorted modes, making the approach simple and robust. The network results in the generation of various mode profiles at the transmitter that, after propagation through turbulence, closely resemble the desired target mode. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 23 publications
0
63
0
2
Order By: Relevance
“…In [302], Li et al presented a technique for the detection of atmospheric turbulence and adaptive modulation using CNN achieving high accuracy for different numbers of LG modes. Lohani and Glasser designed a feedback scheme based on CNNs to precorrect OAM profiles at the transmitter end before propagating through turbulent atmosphere, which significantly enhanced the identification process at the receiver end [303]. Authors in [304] proposed the use of CNN to detect OAM beams subject to turbulence and misalignment errors between the transmitter and the receiver.…”
Section: Machine Learning-based Oam Recovery Approachmentioning
confidence: 99%
“…In [302], Li et al presented a technique for the detection of atmospheric turbulence and adaptive modulation using CNN achieving high accuracy for different numbers of LG modes. Lohani and Glasser designed a feedback scheme based on CNNs to precorrect OAM profiles at the transmitter end before propagating through turbulent atmosphere, which significantly enhanced the identification process at the receiver end [303]. Authors in [304] proposed the use of CNN to detect OAM beams subject to turbulence and misalignment errors between the transmitter and the receiver.…”
Section: Machine Learning-based Oam Recovery Approachmentioning
confidence: 99%
“…Zhao et al further demonstrated the potential of a CNN method for the detection of OAM modes subject to turbulence and misalignment, using simulated data [22]. Turbulence regression CNN is reported in [23], where the estimated turbulence impairment is fed back to the transmitter in order to achieve impairment-free transmission of OAM modes. A CNN classifier was used in [24] to detect 21 laboratory-generated HG modes with different input beam parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Our work makes significant steps forward with respect to previous endeavours: while Refs. [53][54][55][56][57][58] leverage NNs to process OAM states, our work is the first to tackle VVBs. Moreover, owing to the variety of techniques we deploy, we can address both classification and regression tasks, thus enabling the reconstruction of the input states in relevant cases of structured light beams.…”
mentioning
confidence: 99%